THE EFFECT OF CARROT FLOUR ADDITION (Daucus carota L.) TO THE QUALITY OF DRY SMALL SHRIMP (Acetes erythraeus) NUGGET - Phopy Dwi Pratiwi; Suparmi Suparmi; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe purpose of this research is to determine the effect of carrot flour addition (Daucus carota L.) to the quality of dry small shrimp (Acetes erythraeus) Nugget. The method used with an experimental method ie to do nugget processing of raw materials for 400g of dry small shrimp with each addition of different carrot flour consist by each treatment levels. The design used was a non-factorial Completely Randomized Design consist of 4 levels ie N0 0% (75g tapioca flour 0g carrot flour), N1 5% (75g tapioca flour 20g carrot flour), N2 10% (75g tapioca flour 40g carrot flour), N3 15% (75g tapioca flour 60g carrot flour). Based on the research, the effect of carrot flour addition to the quality of dry small shrimp nugget was significantly affect to the organoleptic value, moisture, ash, protein, fat, crude fiber, and calcium contained. The result showed was the best treatment to produce the highest on N3 with carrot flour addition 15% (75g tapioca flour and 60g carrot flour) with characteristics golden yellow appearance (7,32), very specific of dry small shrimp (7,24), savory taste (7,32), solid and compact texture (7,56), analysis of moisture, ash, protein, fat, crude fiber and calcium content were 41,84%, 2,04%, 13,92%, 2,00%, 2,03%, 29,68%. Keywords: calcium contained, carrot flour, dry small shrimp nugget